Upaya Meningkatkan Motorik Kasar Melalui Permainan Tradisional Pada Peserta Didik - Gusti Ngurah Arya Yudaparmita; Komang Surya Adnyana (STAHN Mpu Kuturan Singaraja, 2021)
Education is an institution where a person will get experience and learning that has not been known before so that it will be obtained at educational institutions. The level of education in Indonesia has now been developed from the level of Early Childhood Education to tertiary institutions. The gross motoric development of children at the PAUD level is still very low, it can be seen from the level of activity of children to move their bodies. These problems arise possibly because the teacher's knowledge of strategies and games that can be used to develop children's motor skills is still lacking. One of the traditional games that can be used to train and develop gross motor skills in early childhood The learning strategy used by the teacher is through an approach that underlies child-centered learning.